(untitled) (Research, Society and Development, 2022)
In the dental clinic, it is common the dispersion of aerosols and droplets during the practice of procedures, through oral secretions, to the surfaces of benches and dental equipment. These biological secretions may contain pathogenic microorganisms that pose a risk of cross-contamination within the dental environment. Based on the risks and concern for the safety of professionals and patients, the objective of this research was to analyze the surfaces of the environment of a dental school clinic in the north of Tocantins, regarding dirt and the presence of microorganisms after use, cleaning and disinfection. For the analysis, the clinical care box was selected by drawing lots, and it was verified if there was dirt using visual inspection and microbiological contamination of the surfaces: reflector handle, triple syringe, sucker, spittoon, auxiliary table, sink faucet, and box partitions behind the operator and assistant. Analysis followed by microbiological growth in BHI and Nutrient Agar Culture, and by microscopic analysis. Among the surfaces evaluated, the presence of dirt was observed, such as handprints and solid residues. And, also, microbiological growth, with the presence of bacterial morphotypes related to the genera that reside mainly in the oral microbiota. Therefore, it is concluded that the clinical environment had contaminated surfaces even after cleaning and disinfection.